2022
DOI: 10.1007/s10825-022-01899-5
|View full text |Cite
|
Sign up to set email alerts
|

High-performance surface plasmon resonance-based photonic crystal fiber sensor with four open surface rings

Abstract: In this paper, a photonic crystal fiber sensor is proposed which have four-opening channels that support surface plasmon resonances. By detecting the optical spectrum of leakage from the fiber core to the four regions created on its periphery, the sensitivity of the sensor can be assessed. Gold is used as the plasmonic material in the infrared wavelength range on the Titanium oxide film which is used as a substrate layer to increase the coupling and adhesion. Influences of structural parameters on the sensor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The sensor can detect the analyte RI from 1.30 to 1.42. Next, Table 1 compares the RI detection ranges of several PCF-based SPR sensors [15][16][17][18][19][20] . It can be observed that the detection range of our proposed sensor is significantly optimized and improved compared to other reported results.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…The sensor can detect the analyte RI from 1.30 to 1.42. Next, Table 1 compares the RI detection ranges of several PCF-based SPR sensors [15][16][17][18][19][20] . It can be observed that the detection range of our proposed sensor is significantly optimized and improved compared to other reported results.…”
Section: Simulation Results and Discussionmentioning
confidence: 99%